Geeks and Newbies: Investigating the Criminal Expertise of Online Sex Offenders. Issue 4 (3rd April 2023) - Chopin, Julien; Paquette, Sarah; Fortin, Francis
ABSTRACT: While online sex offenders use a wide range of strategies to try to avoid police detection, attempts to avoid detection of child sexual exploitation materials (CSEM) and online sexual solicitation of children have received very little attention. This study aims to understand online sex offenders' behaviors by modeling the factors associated with their use of technological data protection and anonymity preservation strategies. The data is based on a sample of 199 men involved in crimes related to the use of child pornography or sexual solicitation of minors online. The analytical strategy based on the use of an artificial neural network (ANN), a machine-learning system, identified two trends. First, those who displayed problematic substance use and sexual thoughts and fantasies as well as behaviors reported to be preoccupying did not use specific strategies to avoid police detection. Second, two combinations of factors predict use of police anti-detection strategy, suggesting that the criminal expertise of online sex offenders is manifested in two different patterns: those building on existing knowledge, and those learning skills through previous judicial experience.